PEMBELAJARAN KOSAKATA DALAM PENDIDIKAN SAINS: TINJAUAN SISTEMATIS TERHADAP STRATEGI PENGAJARAN BAHASA INGGRIS: Vocabulary Learning in Science Education: A Systematic Review of English Language Teaching Strategies - I Gusti Ngurah Octova Seventilofa (Yayasan Al-Amin Qalbu, 2026)
Vocabulary mastery plays an important role in supporting students' achievement in both English language learning and science education. However, many English as a Foreign Language (EFL) learners struggle to understand scientific concepts due to their limited knowledge of science-related vocabulary. Various English Language Teaching (ELT) strategies have been introduced to address this issue, but previous findings remain fragmented across different educational contexts and research designs. Therefore, this study aims to systematically review recent literature on ELT strategies for improving science vocabulary learning. This study employed a Systematic Literature Review (SLR) following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Empirical studies published between 2020 and 2025 were collected from Scopus, ERIC, ScienceDirect, SpringerLink, and Taylor & Francis. The selected articles were screened using predetermined inclusion and exclusion criteria and analyzed thematically. The findings indicate that explicit vocabulary instruction, Content and Language Integrated Learning (CLIL), inquiry-based learning, digital learning technologies, game-based learning, and artificial intelligence (AI)-assisted learning consistently improve students' science vocabulary. These strategies also contribute to better reading comprehension, scientific literacy, learning motivation, and classroom engagement. Overall, integrating language instruction with science learning provides meaningful opportunities for vocabulary development in EFL contexts. The findings offer practical insights for English teachers, science educators, curriculum developers, and future researchers in developing more effective interdisciplinary teaching practices